Enhancing Employee Performance through Conflict Management, Work Environment, and Leadership Style - Sapruwan, Muhammad (Lentera Ilmu Nusantara, 2024)
This research investigates the effects of workload and work-related stress on employee performance. Utilizing a quantitative methodology, the study applied a probability sampling technique, specifically simple random sampling, to collect data from employees via a digital questionnaire. The analysis was conducted using advanced statistical tools supported by SmartPLS 3.0 software. The results demonstrate that both workload and work stress significantly influence employee performance. While these factors contribute positively to productivity, the study emphasizes the necessity of maintaining balanced workload and manageable stress levels to ensure sustained optimal performance. Furthermore, the research recognizes the potential impact of other external variables that may also affect employee performance, which were not included within the study's scope.